Treasury of Norse mythology : stories of intrigue, trickery, love, and revenge - Napoli, Donna Jo, 1948- (National Geographic, 2015)
Presents a collection of eighteen Norse myths including "Odin's Quest," "Freyja's Shame," and "The Gods Take Vengeance."